A Vocational English Teacher’s Professional Identity in Industry 4.0 - Setyowati, Insyavia Rahayu; Drajati, Nur Arifah (Universitas Islam Negeri Raden Intan Lampung, 2021)
The growth of technology in Industry 4.0 also gives an impact on education. Language teachers are not only consumers of commercial educational materials, but also must improve creativity in managing classrooms. They should find innovative instructional approaches, methods, and strategies. Therefore, the language teacher identity (LTI) becomes very important. The teachers should discover the contexts in which their designed practices are rooted and expelled to criticize their own personal and professional lives. The current article is a narrative inquiry that an English teacher of vocational high school in Indonesia began to experience over a period of two years during which she could see herself trying to find the best English learning for students that are ready to work in industry 4.0. Shimmering on self experiences and documenting the activities narratively made the teacher face with a number of teaching tradition that she wants to bridge education to world current development. With the development of technology, She began to see herself transforming from traditional learning into new learning that well matched for millennial students. These experiences become very challenging for teachers who are interested in self-inquiry research.